Understanding the effect of solvent vapor annealing on solution-processed A–D–A oligothiophene bulk-heterojunction solar cells: the role of alkyl side chains. Issue 7 (27th January 2016) - Wessendorf, Cordula D.; Perez-Rodriguez, Ana; Hanisch, Jonas; Arndt, Andreas P.; Ata, Ibrahim; Schulz, Gisela L.; Quintilla, Aina; Bäuerle, Peter; Lemmer, Uli; Wochner, Peter; Ahlswede, Erik; Barrena, Esther
Abstract : Solvent vapor annealing (SVA) can strongly influence the morphology of oligomer:fullerene based organic solar cells. Abstract : Solution-processed bulk heterojunction solar cells consisting of the previously developed dithienopyrrole containing A–D–A oligothiophenes (A = acceptor, D = donor unit) and [6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM) with power conversion efficiency up to 7.1% after solvent vapor annealing (SVA) are demonstrated. The influence of the position of the alkyl side chains attached to the thiophene units on the SVA, and the usage of either PC61 BM or PC71 BM as acceptor, is investigated in more detail by negative secondary ion mass spectrometry (SIMS), Kelvin probe force microscopy (KPFM), photoluminescence (PL), and grazing-incidence X-ray diffraction spectroscopy (GIWAXS). It was found that besides increased crystallinity and domain sizes, the active layers consisting of two different isomers which we will refer to in the following as isomer1 or isomer2 had different compositions after SVA treatment. In the former, a more or less homogeneously-mixed D:A blend was observed, whereas the latter showed a vertical gradient of PCBM in the active layer and much stronger phase segregation on the surface. These findings correlate well with the differences in solar cell performance of both isomers, before and after SVA.